8.3 Placental growth factor (PLGF) and ultrasound parameters for predicting the small for gestational age infant (SGA) in suspected small for gestational age: pelican FGR study. (9th June 2014) - Griffin, MJ; Seed, PT; Webster, LM; Tarft, H; Chappell, LC; Shennan, AH
Abstract : The SGA infant is at increased risk of short and long-term health complications. Identifying the SGA fetus remains challenging. Placental insufficiency contributes to pathogenesis and it has been proposed that markers of placental function such as PlGF may improve prediction. PELICAN FGR, a large multicentre, prospective observational study measuring PlGF in women with reduced symphysis fundal height (SFH), assessed the ability of PlGF and ultrasound parameters to predict delivery of an SGA infant. 592 women with singleton pregnancies and reduced SFH between 24–37 weeks' gestation across 11 sites in UK and Canada were analysed. Plasma PlGF was measured at enrolment and ultrasound data recorded. Plasma PlGF concentration <5 th centile, estimated fetal weight <10 th centile (EFW10), umbilical artery Doppler pulsatility index > 95 th centile and oligohydramnios were compared as predictors for an SGA infant <3 rd (SGA3) and <10 th (SGA10) customised birthweight centiles. Test performance statistics were calculated for all parameters in isolation and combination. Sensitivity and negative predictive value (NPV) of EFW10 for SGA3 (n = 78) were 61% and 93% respectively; for SGA10 (n = 192) they were 49% and 77% respectively. PlGF had sensitivity of 37% and NPV of 90% for SGA3. In combination, PlGF and EFW10 had sensitivity of 69% and NPV of 93% for SGA3. In women presenting with reduced SFH, EFW10 and other ultrasound parameters have modest test performance for prediction of a subsequent SGA infant. PlGF performed no better than EFW10 in determining delivery of an SGA infant. Incorporating PlGF with ultrasound parameters provided modest improvements in test performance.